L`idéal du laisser-agir (wuwei) dans les pratiques martiales chinoises: quelle place pour le soi dans l`action efficiente? - Legendre, A. (Movement & Sport Sciences - Science & Motricité, 2018)
Many Asian body practices have been developed on an expertise based on the combination of two principles that can appear contradictory from a western point of view: self-cultivation (xiuyang) and self-surrender through the laisser-agir (wuwei). Chinese martial arts provide a clear illustration of this phenomenon: through repetitions, the athlete improves his skills and becomes able to switch from reflexive consciousness to body consciousness to execute his techniques. In the case of Chinese martial arts, this body consciousness is rooted/grounded in the haptic sense. Freed/Emancipated from the control of consciousness, techniques are led by a motor unconsciousness: the sedimented experience that acts according to the natural of its own spontaneity (ziran). Then, the self, released from consciousness and coextensive with his acquired ability (his gongfu), is redefined in such a way that makes it coincide with the functioning of things, the dao. If the West did not couch it in the same language, it does not ignore anymore, thanks to modern sciences, how limited is the contribution of reflexive consciousness to skill acquisition.